A qualitative study of Green HRM practices and their benefits in the organization: An Indonesian company experience - Lieli Suharti; Agus Sugiarto (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Green Human Resource Management (HRM) aims to shape employee behavior to help organizations achieve their environmentally-friendly goals. Firms can translate the implementation of Green HRM concept into each HRM function. This paper is qualitative exploratory research that investigates the implementation of Green HRM in a company located in Indonesia that is internationally reputable for being an environmentally friendly company. This study aims to highlight the implementation of Green HRM through various HRM functions and to analyze the positive impacts of the implementation of Green HRM on individuals and organizations. The results demonstrated that the implementation of Green HRM provided benefits for individual employees and the company as well. In particular, individual employees had better green and non-green work outcomes. Meanwhile, at the organizational level, the benefits of the implementation of Green HRM were the creation of environmentally friendly organizational culture and work climate, the increased efficiency of various resources, the formation of positive corporate image and increased economic and eco-performance. It is expected that this study contributes to extend the literature on the implementation of Green HRM and its benefits to companies.
Keywords: J53; M54; Q56; 650; Green Business; Green HRM; individual benefits; organizational benefits; corporate sustainability